RESEARCH ON THE FATIGUE PERFORMANCE OF HELICAL GEAR PAIR BASED ON LOAD SPECTRUM - ZHANG YanJie; WU XunCheng; ZHANG JueCheng (Jixie qiangdu)
The 3D contact finite element model of helical gear pair is built to generate mode neutral file by ANSYS,the flexible dynamics simulation anslysis is carried out by using ADAMS,and contact force of helical gear pair is obtained as load spectrum. The fatigue life of the helical gear pair is performed by using nCode based on load spectrum,stress-strain of helical gear pair under contact analysis in ANSYS and the S-N curve of helical gear pair. Meanwhile,the 3D model of helical gear pair with tooth profile deviation is established to study teh influence of tooth profile deviation to fatigue life of helical gear pair. The results show that the fatigue life decrease of helical gear pair with the increase of tooth profile deviation.